OCCUPATIONAL SAFETY AND HEALTH OF CONSTRUCTION PROJECTS IN DILI, TIMOR LESTE - Maria Madalena De Jesus Soares; Kurniawan (NAROTAMA UNIVERSITY, Indonesia, 2022)
Occupational Safety and Health is the program to protect workers from the dangers of work accidents and occupational diseases that may occur during work. This study was conducted to determine the implementation performance of occupational safety and health program, to find out the obstacles during the implementation occupational safety and health programs, as well as labor laws and regulations relating to OSH on construction projects in Dili Timor Leste. This study collected data by distributing questionnaires to employees who work on the four (4) ongoing construction projects in Dili. Data analysis was carried out on Microsoft Excel which further processed the data using the mean count to determine the average value of the questionnaire and the standard deviation. This study found that the project in Dili has implemented the Occupational Safety and Health program. This can be seen from the overall results of the analysis with a mean value of 4.49 and a standard deviation of 0.473. From these results, it can be concluded that every construction project company prioritizes the implementation of OHS. The second result is the obstacles in applying OHS; from the analysis results show that the barriers from the worker side are rank 1 with a mean value of 2.90 and a standard deviation of 0.925. It can be concluded that many obstacles in implementing the OSH program occur from the workers' side due to the lack of awareness and knowledge of workers about OSH in working on construction projects. The result of the third analysis is Timor Leste's labor laws and regulations. The results of the analysis show that it is sufficient for companies to apply Law no. 4/2012 on employment in the areas of security, hygiene and health in the workplace.